1995
DOI: 10.1074/jbc.270.36.21114
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Binding Site for Phosphatidylinositol 4,5-Bisphosphate on Human Profilin

Abstract: Profilin is a small 12-15-kDa actin-binding protein, which in eukaryotic organisms is ubiquitous and necessary for normal cell growth and function. Although profilin's interactions with its three known ligands (actin monomers, phosphatidylinositol 4,5-bisphosphate (PIP 2 ), and poly-L-proline (PLP)) have been well characterized in vitro, its precise role in cells remains largely unknown. By binding to clusters of PIP 2 , profilin is able to inhibit the hydrolysis of PIP 2 by phospholipase C␥1 (PLC␥1). This abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
105
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 48 publications
(68 reference statements)
17
105
0
Order By: Relevance
“…Table S1 summarizes how each of these mutations affects various ligand interactions of profilin1, as determined by quantitative and nonquantitative binding assays in previous studies [only phosphoinositide binding of H119E-profilin1 was not specifically tested previously; we qualitatively confirmed that H119E substitution does not impair profilin1's phosphoinositide binding (Fig. S1), and this is consistent with a previously reported finding for the analogous H119D mutant (15)]. In summary, H119E and H133S substitutions selectively abolish profilin1's interaction with actin (25-fold lower binding than WT) and polyproline ligands (50-fold lower binding than WT), respectively (16).…”
Section: Profilin1 Inhibits Mda-mb-231 Cell Motility Predominantly Thsupporting
confidence: 79%
See 2 more Smart Citations
“…Table S1 summarizes how each of these mutations affects various ligand interactions of profilin1, as determined by quantitative and nonquantitative binding assays in previous studies [only phosphoinositide binding of H119E-profilin1 was not specifically tested previously; we qualitatively confirmed that H119E substitution does not impair profilin1's phosphoinositide binding (Fig. S1), and this is consistent with a previously reported finding for the analogous H119D mutant (15)]. In summary, H119E and H133S substitutions selectively abolish profilin1's interaction with actin (25-fold lower binding than WT) and polyproline ligands (50-fold lower binding than WT), respectively (16).…”
Section: Profilin1 Inhibits Mda-mb-231 Cell Motility Predominantly Thsupporting
confidence: 79%
“…It was previously reported that phosphoinositide binding of profilin1 can inhibit phospholipase-Cγ (PLCγ)-mediated PI(4,5)P 2 hydrolysis in vitro (7,15). These findings led to a speculation that profilin1 could be a phosphoinositide regulator, but it was never confirmed in vivo.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Eight of the most highly conserved residues in eukaryotic profilins ( Thorn et al, 1997), marked with asterisks in Figure 1, have been implicated in PLP binding by using mutagenesis (Björkegren et al, 1993;Haarer et al, 1993), nuclear magnetic resonance spectroscopy (Metzler et al, 1994; Domke et al, 1997), and x-ray crystallography (Mahoney et al, 1997). The hydroxyl group of tyrosine-6 was shown to interact directly with the backbone of the PLP peptide (Mahoney et al, 1997), and the Y6F mutation in human profilin I was shown to elute from PLP-agarose at a lower concentration of urea than did the wild-type protein (Sohn et al, 1995). Therefore, the observation that the ZmPRO1-Y6F mutant has higher affinity for PLP is somewhat surprising.…”
mentioning
confidence: 99%
“…The binding domains of actin and actin related proteins (blue; Schutt et al, 1993) and PtdIns 4,5-P2 (red; Sohn et al, 1995) overlap, while that for proline-cluster sequences (green; Metzler et al, 1994) is located at the opposite side of the profilin molecule, adapted from Schlüter et al, (1997) with permission.…”
Section: Ligands Binding Sitesmentioning
confidence: 99%